Evaluation of cardiac dynamics by a mathematical law in 16 hours: application to 400 cases - Javier Oswaldo Rodríguez Velásquez; Guillermo Orlando Trout Guardiola; Signed Esperanza Prieto Bohórquez; Ribká Soracipa Muñoz; Jairo Javier Jattin Balcázar; Ediltrudis Ramos de la Cruz (Universidade Estadual de Maringá, 2022)
To corroborate the clinical application of an exponential mathematical law based on dynamic systems by reducing its evaluation time to 16 hours through a diagnostic concordance study with respect to the clinical conventional diagnosis. A blind study was carried out with 400 cardiac dynamics with continuous electrocardiographic recordings and Holter records, of which 150 correspond to normal patients and 250 to patients with cardiac alterations. For this, chaotic attractors of cardiac dynamics were constructed with which the fractal dimension and its spatial occupation in the generalized Box-Counting space were calculated. For normal cases, occupancy spaces between 85 and 354 were found for the Kp grid and between 45 and 342 for cases with pathologies in 16 hours, differentiating through this parameter from normality of disease. The sensitivity and specificity were 100% and the kappa coefficient was 1 when making the comparison between the diagnosis using the physical-mathematical methodology in 16 hours and the Gold Standard. The results demonstrated that by reducing its evaluation time, the exponential mathematical law diagnosed cardiac dynamics in 16 hours with the same precision as in 21 hours, corroborating its clinical applicability.